Program Penguatan Hafalan Al-Qur’an Bagi Siswa Sekolah Dasar Qur’an Al-Bayan Subang - Rani; Apri Wardana Ritonga; Desriliwa Ade Mela; Saniwa (STIT Fatahillah, 2023)
This study aims to find out how the process of strengthening the memorization of the Qur'an for Al-Bayan Subang Elementary School Qur'an. This research uses a qualitative approach with a case study method. The research data was sourced from students and teachers of Al-Bayan Subang Elementary School of Qur'an. The results of this study indicate that the process of strengthening memorization is as follows: First, memorizing the Qur'an is an obligation for all Muslims, because memorizing is one of the ways to maintain the purity of the Qur'an; second,There are several methods to maintain the sanctity of the Qur'an muraja'ah, sima'an, teach it, listen to murotal, and tasmi; third, obstacles in memorizing the Qur'an become influential, including several factors, namely laziness, sleepiness, unsupportive environment, busy with things that are not useful, busy with other activities, not consistent in memorizing, and the influence of the closest people. Techniques for analyzing the results of interviews using direct techniques to gather information from sources. With this research method that we propose can find out information or how to memorize what is in Al-Bayan Subang Qur'an Elementary School This. Memorizers of the Qur'an are required to muraja'ah memorize it because it will support the quality of their memorization achievements. This needs to be optimized by thememorizers of the Qur'an considering the many factors that will affect the loss of the memorization. Through habituation or muraja'ah in memorizing the Al-Qur'an can maintain the memorization that has been memorized.